Pengembangan Profesi Guru Profesional - Rifky, Rifky Aditya Ramadhan (Business Finance Analyst Co., 2023)
This is a description of the professional development of the teaching profession. This research uses a literature review, the type of data used is secondary data. The data collection method is literature study. The method that will be used for this assessment is literature study. The data obtained is compiled, analyzed and concluded so as to obtain conclusions regarding the literature study. The data collection method is by taking data from the library, reading, taking notes and processing research materials. The results of the research show that professional development has been facilitated by the government but awareness from teachers is still lacking. even though teachers have functional positions, where this job requires teachers who are professional and have professional rules. Moreover, a teacher has a big responsibility, and has positive values ​​and has a contribution to life in wider society towards the progress of students for life in the future.